Pharmacokinetics and anticoccidial activity of ethanamizuril in broiler chickens - Fu, Yikai; Zhou, Junwen; Zhang, Lifang; Fei, Chenzhong; Wang, Xiaoyang; Wang, Mi; Wang, Chunmei; Zhang, Keyu; Xue, Feiqun; Liu, Yingchun (Veterinary parasitology, 2021)
•The concentrations of ethanamizuril in chicken cecal contents were detected.•The pharmacokinetic parameters of ethanamizuril in contents were analyzed.•Anticoccidial efficacy of ethanamizuril to challenged chickens was evaluated. The treatment effect of ethanamizuril (EZL) to broiler chickens experimentally infected with 8 × 104Eimeria tenella was evaluated. On the third day after infection, the broiler chickens were treated with EZL by gavage at doses of 2, 4, and 8 mg/kg body weight (bw) for once. For double administration, the challenged broiler chickens were administered EZL at doses of 1, 2, 4, and 8 mg/kg bw by gavage continually on the third day and fourth day and once a day. Throughout the experimental period, performance parameters including body weight gain, mortality, cecal lesion score, bloody diarrhoea and oocyst output were recorded. The anticoccidial efficacy was evaluated using the anticoccidial index (ACI). Meanwhile, the concentrations of EZL in chicken cecal contents were measured, and the data were analyzed with a non-compartmental model. The results indicated that EZL showed good anticoccidial activity at single dose of 4 mg/kgbw, with the corresponding ACI of 175.73. When the challenged chickens were treated with EZL under double administration, the EZL showed a medium level of anticoccidial activity at a dose of 2 mg/kg bw, with the corresponding ACI of 162.48. The maximum concentrations (Cmax) of EZL in content were 2.43 ± 1.16, 4.28 ± 1.56, and 8.57 ± 1.33 mg/kg after the chickens were administrated at doses of 2, 4, and 8 mg/kg bw, respectively. The respective areas under the curve were 36.93 ± 8.91, 96 ± 16.31, and 262.76 ± 51.52 mg/kg h. The respective half-lives (T1/2) were 10.82 ± 2.02, 10.53 ± 2.23, and 10.60 ± 1.50 h. The results show that when the concentrations of EZL in chicken cecal contents reached 4.28 ± 1.56 mg/kg, there is a significant therapeutic effect on chicken coccidiosis.